The Philippine independence movement, 1921-1946 an annotated bibliography of documents found in the United States Congressional Record and in other sources (66th Cong., 3rd sess. - 79th cong., 2nd sess.) - Cruz, Theresa B.; Manuel, E. Arsenio; Hidalgo, Namnama P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1980)
As a solution to bibliographical tool deficiency due to almost complete non-availability in the Philippines of American Congressional documents on the Philippine independence movement, this historico-bibliographical work attempts to satisfy the needs of scholars in their researchers in this regard.
The period from 1921 to 1946 was one of the most trying times in the struggle for Philippine Independence and the politics of nationalism. The year 1921 is selected as the chronological starting point for this bibliography because of its significance in terms of the Filipinos' struggle after a period of relative peace and positive collaboration during the administration of Governor-General Francis B. Harrison, which was preceded by the traumatic Filipino-American conflict at the turn of the century. For one, 1921, witnessed a change in administration both in the United States and the Philippines. The American progressive liberal tradition symbolized by President Woodrow Wilson was reflected by his proconsul in the Philippines, the Tamany hall politician turned liberal, Francis Burton Harrison. Governor-Genral Harrison's liberal and positive administration under which he allowed the Filipino leadership to control the government was replaced by the conservative and negative tradition of general Leonard Wood. Wood, not surprisingly, was sent by a conservative party which replaced the Democratic Party at the helm of the American government -- the Republican Party -- thereby ushering a new era of reaction and conservatism, and of course President Warren G. Harding.
The advent of conservatism in the Philippines in 1921 was reflected in the policy of check and balance, and other myths of the American strain of conservatism within a liberal framework. The period saw the attempt to preserve the conservative concept of separation of powers among the three branches of government with, however, a racial and political overtone. The Americans, as colonizer, should control the executive and judicial branches, while the Filipinos as the colonized would be confined to the legislative branch. This strict constitutional construction of the Jones Law of 1916 was naturally interpreted by the Filipino leadership as an attempt to stifle nationalism and a devolution policy toward more American control -- a regressive step away from independence.
For another, the decade of the 1920's looked bad for the Filipino elite leadership as the spectre of Japan's threat, the attempt of separating Mindanao and Sulu archipelago, and the domestic prosperity that further entrenched foreign vested interests in the country, combined to make the situation difficult and frustrating for the nationalists. Nevertheless, the political crisis marked a renewal of demand for freedom from colonial control as manifested by the increased volume of literature on independence in the first half of the thirties.
The year 1946 represents the culmination of the Filipino struggle for independence although there were pressures to the contrary, both objective and subjective. The chronological coverage of our study in general shows intersting historical pattern from frustration and disappointment because of Wood's conservatism to triumphant nationalism as the American government officially became committed to a policy of granting independence after a Commonwealth period of ten years. Nineteen forty six, therefore, marked the realization of the goal of independence, which was implicit in the Jones Law and explicit in the Tydings-McDuffie law as America's moral and political commitment.
Since this work starts in 1921, it is suggested, as a sort of follow-up, that another historico-bibliographical study be made for the earlier period, 1898-1920, to complete the coverage of the American administration in the Philippines.
This bibliography is chronologically arranged according to Congress, session numbers, date when the document was entered in the Congressional Record. It comes in two volumes. The first volume is composed of three parts. Part one lists Public Laws, Proclamations and Treaties and parts two and three list House and Senate Bills, Documents, Reports and Resolutions. The second volume which makes up part four of this work is composed of the Extension of remarks.
Each of the 1,611 entries is preceded by a code or entry number which is utilized as the indexing reference. With some modifications, the guide used for procedural and stylistic purpose is the Bibliographical Procedures and Style (1954), a manual for the bibliographers of the Library of Congress and used by many other libraries.
Thesis (M.L.S)--University of the Philippines, Diliman
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Philippines--Commonwealth--Bibliography.; Philippines--Foreign relations--United States; Philippines--History--1898-1946--Bibliography.; Philippines--Politics and government--1898-1935--Bibliography.; Philippines--Politics and government--1935-1946--Bibliography.; United States--Foreign relations--Philippines.